BTEX chrono-metabolism and leukemogenic effects of night shift work in workers of gasoline stations: the EXPOSOWORK prospective panel study in Bulgaria - Heibati, Behzad; Soursou, Georgia; Abimbola, Samuel Olushola; Charisiadis, Pantelis; Eleftheriou, Lygia; Berge, Leon A M; Stenehjem, Jo S; Makris, Konstantinos C. (My University, 2025)
Exposures to benzene, toluene, ethylbenzene and xylenes (BTEX) have been associated with impairment of the hematopoietic system, often leading to leukemogenesis. A prospective panel study: i) characterized the effect of night shift work (NSW) (12-hr night shift vs. 12-hr day shift) on urinary BTEX and metabolites in gasoline station workers in Plovdiv, Bulgaria, ii) evaluated the NSW effect on chrono-based BTEX genotoxic effects (as measured by 8-OHdG, a nonspecific biomarker of genotoxicity) including the influence of the downstream urinary metabolome.
Keywords: BTEX; Circadian rhythm; Exposome; Leukemia; Metabolomics; Night shift